2016
DOI: 10.1111/imj.13173
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of benzbromarone in gout in Aotearoa New Zealand

Abstract: Benzbromarone provides useful urate-lowering efficacy and does not appear unsafe in patients with gout. Urate-lowering therapy prescribing requires further optimisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 10 publications
(21 reference statements)
2
18
0
Order By: Relevance
“…Benzbromarone has been reported to have a serious side effect in terms of adversely affecting hepatic function, but no such side‐effects were observed in this study. This supports a prospective study in New Zealand that showed benzbromarone led to minimal adverse liver events . These results also suggest that allopurinol and benzbromarone cause no significant adverse reactions.…”
Section: Discussionsupporting
confidence: 88%
“…Benzbromarone has been reported to have a serious side effect in terms of adversely affecting hepatic function, but no such side‐effects were observed in this study. This supports a prospective study in New Zealand that showed benzbromarone led to minimal adverse liver events . These results also suggest that allopurinol and benzbromarone cause no significant adverse reactions.…”
Section: Discussionsupporting
confidence: 88%
“…In our literature search, we found several other studies published in or after 2008 that directly or indirectly evaluated the safety of benzbromarone [19-21, 26, 28, 37-39]. Among these, a one-year prospective analysis of 123 patients in New Zealand and a three-year Chinese retrospective study both reported no serious events related to benzbromarone treatment [19,21]. Two other systematic reviews reported similar results [20,38].…”
Section: Studies Evaluating Benzbromarone's Safetymentioning
confidence: 86%
“…Several studies and meta-analyses have demonstrated benzbromarone's efficacy in reducing sUA levels and preventing gout flares. The usual dosage varies between 50 mg and 200 mg daily [16,[19][20][21].…”
Section: Efficacy Evidencementioning
confidence: 99%
See 2 more Smart Citations